Creating a Collaborative Learning Community for Aboriginal and Torres Strait Islander Health Promotion Students : Enhancing Access, Progression and Learning in Higher Education : Final Report. - Dickson, Michelle (Office for Learning and Teaching, 2014)
Final report from a project that was undertaken in 2012 and 2013 and focused on bringing Graduate Diploma in Indigenous Health Promotion (GDIHP) alumni back to teach and mentor current GDIHP students. Each teaching Block, one or two GDIHP alumni spent two days with the students discussing their health promotion work since completing the GDIHP, sharing stories about their journey as a GDIHP student, and providing assessment task and other advice. Many of these alumni are now undertaking Masters and PhDs and are powerful role models. This project addressed the needs of Aboriginal and/or Torres Strait Islander students and teachers of Aboriginal and/or Torres Strait Islander students studying the GDIHP at the University of Sydney. By developing learning partnerships with alumni the project brought together Aboriginal and/or Torres Strait Islander health promotion practical experience and expertise to campus and established collaborations between current students, staff, and alumni. The project met the OLT priority "Strategic approaches to learning and teaching which enhance student access and progression, and respond to student diversity". Specifically, it developed and piloted an innovative approach to enhancing the Aboriginal and/or Torres Strait Islander student progression and experience by embedding collaborative knowledge exchange into the entire program curricula. Positioning collaborative learning as its pedagogical framework and health promotion as its disciplinary foundation, this project modelled how Aboriginal and/or Torres Strait Islander students can develop their intra-cultural and inter-cultural competencies, transform their understandings of their professional culture, and experience academic support through collaborative knowledge exchange with program alumni.